Servant leadership and employee wellbeing: A crosscultural investigation of the moderated path model in Canada, Pakistan, China, the US, and Brazil. (August 2022) - Wang, Zheni; Panaccio, Alexandra; Raja, Usman; Donia, Magda; Landry, Guylaine; Pereira, Michelle Morelo; Ferreira, Maria Cristina
Drawing on samples from Canada, Pakistan, China, the US, and Brazil comprising over 800 employees, we examined whether servant leaders (SL) - characterized as putting the needs of others above their own - promote employees' well-being via autonomous motivation, accounting for employees' power distance and collectivism values as moderating variables. Autonomous motivation, a type of self-regulation, sustains one's well-being. Personal values facilitate one's work behaviors cross-culturally. Multigroup confirmatory factor analysis (CFA) results confirmed matrix invariance of all the measures. The path and moderation analyses result using multilevel structural equation modeling (SEM) supported the positive direct and indirect paths among SL, autonomous motivation, and psychological well-being across the five cultures; Collectivistic value negatively moderated the relationship between servant leadership and autonomous motivation across the Chinese and US samples. In addition, with only a limited number of items, measurements of SL and vitality achieved scalar invariance. ANOVA test results also confirmed the significant comparative differences in these two variables among the cultural groups. Findings in this research provided robust and empirical support for the motivational effects of the servant leadership theory across the globe. Theoretical and practical implications for evidence-based cross-cultural management practices and future directions for leadership training in diverse cultural contexts are discussed.